La Soufriere Volcanic Eruptions Launched Gravity Waves Into Space. Issue 8 (18th April 2022) - Yue, Jia; Miller, Steven D.; Straka, William C.; Noh, Yoo‐Jeong; Chou, Min‐Yang; Kahn, Ralph; Flower, Verity
Abstract: Atmospheric gravity waves can be excited by explosive volcanic eruptions and may reach Earth's upper atmosphere. In this study, we report on mesoscale concentric gravity waves observed in the mesopause airglow layer following the La Soufriere volcano eruption in April 2021. A large ash plume observed by the spaceborne Multi‐angle Imaging SpectroRadiometer instrument on April 10 reached ∼20 km. Temporal evolution of the volcanic ash plume was provided by the GOES‐16 Advanced Baseline Imager. Nightglow gravity waves were observed by the Visible Infrared Imaging Radiometer Suite Day Night Band. These waves had horizontal wavelengths of ∼25–40 km, and took about a half‐to‐1 hr to travel from the tropopause to the mesopause. Some concentric ionospheric disturbance signatures are also seen in Global Navigation Satellite System‐total electron content maps. We found the launch of gravity waves to be highly correlated with the elevated ash plume from explosive eruptions. Plain Language Summary: Explosive volcanic eruptions occur when the pressure of hot gases trapped inside magma builds up, resulting in the rapid injection hot gas and ash many kilometers into the atmosphere, sometimes reaching the stratosphere. Atmospheric gravity waves are excited in this process. Concentric gravity waves observed in the mesopause airglow layer were launched by the La Soufriere volcano explosive eruption in April 2021. A large ash plume on April 10 reached ∼20 km, overshooting the tropopause layer. Nightglow gravity waves observed by the Day Night Band of Visible Infrared Imaging Radiometer Suite instruments on both the Suomi National Polar‐orbiting Partnership and National Oceanic and Atmospheric Administration‐20 satellites reveal concentric patterns. These waves took about a‐half‐to‐1 hr to reach the mesopause. Some concentric ionospheric disturbance signatures are also induced by the volcanic gravity waves. Our observations of this event provide direct evidence of lithosphere‐atmosphere‐ionosphere coupling via the generation and propagation of gravity waves. Key Points: La Soufriere volcanic explosive eruptions in April 2021 excited gravity waves (GWs) propagating into the mesosphere Multi‐angle Imaging SpectroRadiometer detected elevated ash plume after the eruption that overshot the tropopause Concentric ionospheric disturbances in Global Navigation Satellite System total electron content data could be induced by the volcanic excited GWs